“Reports of My Death Are Greatly Exaggerated”: Findings from the TEI in Libraries Survey - Michelle Dalmau (OpenEdition, 2015)
In the early days of the TEI Guidelines, academic libraries extended their access and preservation mandates to include electronic text, providing expertise in authority control, subject analysis, and bibliographic description. But the advent of mass digitization efforts involving simple scanning of pages and OCR called into question such a role for libraries in text encoding. This paper presents the results of a survey targeting library employees to learn more about text-encoding practices and to gauge current attitudes toward text encoding.